Heroic Themes of the Trojan Cycle in Roman Funerary Art: Example of a Relief from Pincum - Pilipović, Sanja (Balcanica - Annual of the Institute for Balkan Studies, 2006)
The fragment of a marble relief from Roman Pincum (modern-day Veliko Gradište, Serbia) showing Achilles and Hector inspires to explore the symbolic meaning of this mythological composition and to examine other reliefs depicting heroic themes of the Trojan Cycle in the funerary art not only of Upper Moesia but also of other provinces of the Empire, notably Noricum and Pannonia. Based on the available data, a reconstruction of the original appearance of the funerary monument with the relief of Achilles and Hector from Pincum is attempted, and the inscription discovered along with it analyzed. Also, the importance of Pincum itself is shown, an archaeological site in the Upper Moesian Limes area which remains insufficiently investigated.